The Lost Kingdom of Tao-Klarjeti - Katharine Vivian (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2023)
The text describes an expedition to Tao-Klarjeti organized by British Museum Tours. The author, together with the group, visited historical Georgian territories located in eastern Turkey and explored significant cultural and architectural monuments, including the Hagia Sophia of Trabzon, the Sumela Monastery, Ishkhani, Bana, and etc